2007
DOI: 10.1021/la702129b
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Guided Templating of Particle Assemblies Inside Drying Sessile Droplets

Abstract: The particles suspended inside evaporating sessile droplets can be assembled into microscopic objects with long-ranged ordered structure. The air-water droplet interface guides the assembly and determines the shape of the resulting micropatches. We report the results of a systematic study of the mechanism of interface-templated assembly on substrates of controlled contact angle. The kinetics of drying were examined by measurements of droplet profiles, and it was found that the rate matched diffusion-limited ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
122
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 56 publications
6
122
0
Order By: Relevance
“…S7). Such a shape is clear evidence of a single drying sessile ink droplet containing mobile nanoparticles 15 and illustrates the accumulation of several smaller droplets on the substrate due to insufficient vapourization rates.…”
Section: Working Principle and Set-upmentioning
confidence: 95%
“…S7). Such a shape is clear evidence of a single drying sessile ink droplet containing mobile nanoparticles 15 and illustrates the accumulation of several smaller droplets on the substrate due to insufficient vapourization rates.…”
Section: Working Principle and Set-upmentioning
confidence: 95%
“…Spherical-cap-shaped colloidal crystals (i.e., nanoparticle clusters) have also been obtained after vaporization-induced volume shrinkage of much larger nanoparticle-laden sessile droplets (22). It is noteworthy, however, that in the present study the concentration increase takes place at an essentially constant volume (i.e., at isochoric conditions).…”
Section: Resultsmentioning
confidence: 56%
“…Previous studies have shown that change in the apparent contact angle with evaporation can lead to change in the flow field of the droplet, and eventually influence the final deposition pattern (Kuncicky and Velev 2008). Under microgravity conditions, the droplet shape changes and tends to be more spherical.…”
Section: Microgravity Conditionsmentioning
confidence: 99%